ChemInform Abstract: Reaction of Acylpyruvic Acid Esters with Hydrazides. Issue 47 (4th November 2013) - Pakal'nis, V. V.; Zerova, I. V.; Yakimovich, S. I.; Alekseyev, V. V.
Abstract 5‐Hydroxy‐2‐pyrazolines are obtained by reaction of hydrazides with acylpyruvic acid esters possessing a terminal straight chain alkyl substituent at the C=O bond distal from the ester group.